Testicular tumors in the boy - Viola, Julio C; Pereyra Bonasso, Jorge; Durante Barbot, Arturo (Cirugía del Uruguay, 1973)
Up to 12 (twelve) years of age, testicular tumors are a rare condition, accounting for 0.5 to 2% of cancers at that age. Bilaterality is even weirder